WT1-guided pre-emptive therapy after allogeneic hematopoietic stem cell transplantation in patients with acute myeloid leukemia - Arai, Shota; Tachibana, Takayoshi; Izumi, Akihiko; Takeda, Takaaki; Tamai, Yotaro; Sato, Shuku; Hashimoto, Chizuko; Fujimaki, Katsumichi; Ishii, Ryuji; Kabasawa, Noriyuki; Hirasawa, Akira; Inoue, Yasuyuki; et al. (International journal of hematology, 2024)
Measurable residual disease (MRD)-guided pre-emptive therapies are now widely used to prevent post-transplant hematological relapse in patients with acute myeloid leukemia (AML). This single-center retrospective study aimed to clarify the significance of pre-emptive treatment based on Wilms’ tumor gene-1 mRNA (WT1) monitoring for MRD in patients with AML who underwent allogeneic hematopoietic stem cell transplantation (allo-HSCT). Patients with AML who received chemotherapy for hematological relapse or WT1 increase after allo-HSCT were eligible for inclusion. From January 2017 to June 2022, 30 patients with a median age of 57 (16–70) years were included and stratified into two groups: 10 with WT1 increase and 20 with hematological relapse. The median times from HCT to WT1 increase or hematological relapse were 309 days (range: 48–985) or 242 days (range: 67–1116), respectively. Less intensive chemotherapy using azacitidine or cytarabine was selected for all patients with WT1 increase and 12 (60%) with hematological relapse. The 1-year overall survival and event-free survival rates for WT1 increase and hematological relapse were 70% vs. 44% ( P = 0.024) and 70% vs. 29% ( P = 0.029), respectively. These real-world data suggest that WT1-guided pre-emptive therapy may be superior to therapy after hematological relapse in patients with AML who have undergone allo-HSCT.